Further rogers-ramanujan identities for split (n +t)-color partitions - Sood G. (Utilitas Mathematica, 2022)
Recently in 2014 the authors introduced a new class of partitions and called them split (n + i)-color partitions and gave combinatorial meaning to two basic functions of Gordon-Mcintosh found in 2000. These new partitions generalize Agarwal and Andrews (n-f color partitions. In this paper we inteipret four Rogers-Ramanujan type identities using spht (n + t)-color partitions. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.